Project management : qualities of construction project manager / Asniza Hamimi Abdul Tharim ... [et al.] - Abdul Tharim, Asniza Hamimi; Azli, Mohd Syhidi; Jaffar, Noraidawati; Shuib, Mohammad Nasharudine; Yusof, Ismail; Ab Wahid, Abdul Muhaimin; Kurdi, Mohd Khairi; Ma'arof, Khairul Anuar (2012)
A project manager is a person who is responsible solely for the management of a project. In certain building construction, the role and responsibility of the project manager is vital in ensuring the success of the project.This paper will provide a conceptual overview of project manager qualities with regards to project management as part of the development process in the construction industry. The objective of this paper is to give an insight into the project manager's roles and qualities in construction development process. Data were obtained through questionnaires distributed to project managers involved in the construction process in 6orth Malaysia. Findings of this study were presented in an integrated tabulated table. Ultimately, this research hopes to contribute to a better understanding on the roles and qualities of a project manager in the construction industry.